Propuesta sobre el proceso productivo para financiar empresas del deporte a partir del estudio de sus seguidores = Proposal on the production process to finance companies sport from studying his followers - Cárdenas-Polanía, Wilson Andrés (Journal of Education, Health and Sport, 2015)
Cárdenas-Polanía Wilson Andrés. Propuesta sobre el proceso productivo para financiar empresas del deporte a partir del estudio de sus seguidores = Proposal on the production process to finance companies sport from studying his followers. Journal of Education, Health and Sport. 2015;5(12):630-646. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.44759 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A630-646 http://pbn.nauka.gov.pl/works/694742 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Cárdenas-Polanía Wilson Andrés. Propuesta sobre el proceso productivo para financiar empresas del deporte a partir del estudio de sus seguidores = Proposal on the production process to finance companies sport from studying his followers. Quality in Sport. 2015;1(4):28-45. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.12.2015. Revised 25.12.2015. Accepted: 29.12.2015. Wilson Andrés Cárdenas-Polanía[1] Facultad de Marketing en la Universidad de Santo Tomás (Bogotá, Colombia) Propuesta sobre el proceso productivo para financiar empresas del deporte a partir del estudio de sus seguidores Proposal on the production process to finance companies sport from studying his followers Resumen El seguidor del deporte debe ser el centro de la operación de las empresas del deporte. Para eso hay que entenderlo y a partir de sus necesidades desarrollar el modelo de negocio que regirá a la empresa del deporte para lograr sostenibilidad financiera. Se plantea una propuesta que se sustenta en la psicología social y la sociología en lo teórico y dos investigaciones en lo metodológico: una descriptiva correlacional transversal y la otra se basa en análisis estadístico de datos textuales. Tomando algunas de sus conclusiones, orientan la propuesta hacia canalizar las necesidades del seguidor del deporte hacia un intercambio denominado consumo cultural. Transita para esto, los elementos necesarios que la empresa debe desarrollar para maximizar emociones, motivaciones e identidades durante los partidos, torneos y eventos deportivos. Lo hace utilizando la amplificación de los valores simbólicos, desarrollar estadísticas y promover la práctica del deporte. Con ese recorrido, surgen actores que deben acompañar el proceso para su éxito: deportistas, medios de comunicación y anunciantes. Con estos insumos se podrá hacer una intersección entre el seguidor y el consumidor del patrocinador. Palabras clave: marketing deportivo, seguidor del deporte, modelo de negocio, necesidades del consumidor Abstract The follower of sport should be the focus of the operation of sport companies. For that we must understand their needs so we can develop the business model that gives direction to the sport company to achieve financial sustainability. The proposal is based on social psychology and sociology at the theoretical part and in two methodological research: A transversal cross-correlation descriptive and the other is based on statistical analysis of textual data. Taking some of its conclusions, the proposal aimed to channel the needs of the follower of sports to an exchange called cultural consumption. For this, the necessary elements that the company must develop to maximize emotions, motivations and identities during games, tournaments and sporting events. It does this using the amplification of symbolic values, develop statistics and promote the practice of sport. With this tour, arise actors that the process for its success must accompany: Athletes, media and advertisers. With these inputs we can make an intersection between the follower and the consumer of the sponsor. Keywords: sport marketing, fan of sports, business model, costumer needs [1] Profesor de la Facultad de Marketing en la Universidad de Santo Tomás (Bogotá-Colombia). Es Candidato a doctor en Administración de Empresas de la Universidad Católica de Argentina (UCA), Magister en Psicología del Consumidor de la Fundación Universitaria Konrad Lorenz (Colombia) y Administrador de Empresas de la Pontificia Universidad Javeriana (Colombia). Ha trabajado en empresas del deporte desde 2000. Mail: proyectos.consultor@gmail.com Twitter: @acardenas74 LinkedIn: co.linkedin.com/in/AndresCardenaspolania